KESESUAIAN PENERAPAN PUTUSAN BEBAS PERKARA TINDAK PIDANA KEKERASAN DENGAN DASAR PEMBELAAN TERPAKSA MENURUT KUHAP - Edwina Prabamawarni; Bambang Santoso (Verstek, 2023)
This article analyzes the criminal procedural law related to the application of acquittals in violent crimes on the basis of forced defense in the provisions of the KUHAP. The Panel of Judges set an acquittal in this case because the Panel of Judges was not sure of the crime committed by the defendant. The purpose of this article is to prove whether the decision of the Pati District Court Number 173/Pid.B/2019/Pn Pti is in accordance with the Criminal Procedure Code. The research method used isdoctrinal or normative legal research. This research is prescriptive and applied. The method of collecting legal materials is by means of literature study and the legal materials used are primary and secondary legal materials. Based on the results of the research and discussion to answer the problem, it can be concluded that the Panel of Judges in establishing an acquittal in the case of the crime of violence against people in the decision of the Pati District Court Number 173/Pid.B/2019/PN Pti complies with the provisions of Article 183 of the KUHAP because the terms of the decision must fulfill the conviction of the judge as stated in the article.Keywords : Free Verdict; Violent Crime; KUHAP